2012
DOI: 10.1021/jo3005815
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Study on HF Elimination and Aromatization Mechanisms: A Case of Pyridoxal 5′ Phosphate-Dependent Enzyme

Abstract: Pyridoxal 5-phosphate (PLP), the phosphorylated and the oxidized form of vitamin B6 is an organic cofactor. PLP forms a Schiff base with the ϵ-amino group of a lysine residue of PLP-dependent enzymes. γ-Aminobutyric acid (GABA) aminotransferase is a PLP-dependent enzyme that degrades GABA to succinic semialdehyde, while reduction of GABA concentration in the brain causes convolution besides several neurological diseases. The fluorine-containing substrate analogues for the inactivation of the GABA-AT are synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…It has been reported that the deprotonation of initial external aldimine M1 and stepwise fluoride elimination steps proposed in Scheme are typically considered as an E1cB elimination mechanism. , The electron-withdrawing effect of fluorine and the protonated nitrogen of the aldimine may stabilize the formed carbanion state during the elimination reaction. , Quinonoid transient state M2 is expected to form between the first and second external aldimines ( M1 and M3 ). However, the stopped-flow experimental results suggest that the antiperiplanar hydrogen and fluorine atoms in M1 undergo a Lys292-assisted E2 mechanism, i.e., concerted loss of a proton fluoride ion, with the formation of the alkene as a more favorable fluoride ion elimination pathway, affording the second external aldimine ( M3 ) directly as the single transient state species ( Pathway e ; Scheme ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the deprotonation of initial external aldimine M1 and stepwise fluoride elimination steps proposed in Scheme are typically considered as an E1cB elimination mechanism. , The electron-withdrawing effect of fluorine and the protonated nitrogen of the aldimine may stabilize the formed carbanion state during the elimination reaction. , Quinonoid transient state M2 is expected to form between the first and second external aldimines ( M1 and M3 ). However, the stopped-flow experimental results suggest that the antiperiplanar hydrogen and fluorine atoms in M1 undergo a Lys292-assisted E2 mechanism, i.e., concerted loss of a proton fluoride ion, with the formation of the alkene as a more favorable fluoride ion elimination pathway, affording the second external aldimine ( M3 ) directly as the single transient state species ( Pathway e ; Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that the deprotonation of initial external aldimine M1 and stepwise fluoride elimination steps proposed in Scheme 6 are typically considered as an E1cB elimination mechanism. 31,32 The electron-withdrawing effect of fluorine and the protonated nitrogen of the aldimine may stabilize the formed carbanion state during the elimination reaction. 32,33 favorable fluoride ion elimination pathway, affording the second external aldimine (M3) directly as the single transient state species (Pathway e; Scheme 6).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Pyridoxine is the metabolite of the vitamin B6 metabolic pathway, and there was a negative correlation between serum pyridoxine level and the risk of CRC [ 43 , 44 ]. Pyridoxine is converted to succinic semialdehyde in the vitamin B metabolic pathway [ 45 ]. The increased succinic acid semialdehyde level suggests that the vitamin B metabolic pathway is an activated state in colorectal cancer tissue, which decreases pyridoxine with protective effects.…”
Section: Discussionmentioning
confidence: 99%
“…The residue Asp298 was reported as an active site residue that interacts with the pyridine ring of PLP via a hydrogen bond. In the literature, the nitrogen on the pyridine ring was depicted both as protonated or unprotonated . In case of a protonated nitrogen, the Asp298 residue should have a side chain with the charge of −1, while in the case of an unprotonated nitrogen on the pyridine ring a neutral Asp298 side chain should be considered.…”
Section: Computational Detailsmentioning
confidence: 99%
“…In the cases of fluorine containing analogues, the reaction starts with a transimination followed by a HF elimination step for the inactivation. Both the experimental and theoretical studies have provided some clues regarding the nature of the catalytic mechanism . Vigabatrin, one of the natural substrate analogues, was reported as the most effective mechanism‐based inactivator of GABA‐AT with a high potency for treatment of epilepsy and it is used in >60 countries .…”
Section: Introductionmentioning
confidence: 99%